PRODUCTIVITY IMPROVEMENT OF STARCH CRACKERS IN KEDUNGKANDANG DISTRICT AS HOME INDUSTRIAL SCALE - Afifuddin, Afifuddin; Wirateruna, Efendi S; Alawiy, Muhammad Taqijuddin (LPPM Univ. Ibn Khaldun Bogor, 2023)
The products produced by Home Industry (IRT) are increasing significantly, one of which is Mr Shodiq's IRT located in Kedungkandang Village, Malang City, East Java. The IRT gathers homemakers to make a product, namely starch crackers with the main ingredients from tapioca flour. The productivity of starch crackers has not increased because the Malang area's weather conditions often rain or are cloudy, even exacerbated by pandemic conditions. Drying of starch crackers still uses the direct drying method under the hot sun and knowledge about the importance of the hygienic process of making starch crackers and product packaging. The methods implemented in this service are socialization, counselling, training, and assistance for IRT. The indicator of the success of IRT community service activities is the formation of 6 cadres of IRT members who can practice the drying process with an oven. The results of drying using an oven dryer require a shorter time of 1 hour with a moisture content of about 8% compared to drying with sunlight which requires about 96 hours. Overcast conditions are around 336-360 hours with a moisture content of 10% for full sun conditions and above 12% for cloudy or rainy conditions.